Coronavirus: valutare o non valutare, quale è il problema? Il rischio da contagio negli ambienti di lavoro - Miscetti, Giorgio; Bodo, Patrizia (La Medicina del Lavoro, 2020)
The article deals with some aspects concerning the relationship between prevention of the risk of coronavirus in the workplace and fulfilments envisaged by Legislative Decree 81/08. More specifically, the issue of the applicability of the risk assessment obligation pursuant to Articles 17,28,29 and 271 of Legislative Decree 81/08 is addressed, against a biological agent, such as coronavirus, which it is not always directly related to the working context. The authors argue that, even where the virus does not constitute a specific work risk factor, an assessment of the working condition, carried out by the same subjects assigned to the risk assessment referred to in Legislative Decree 81/08, is in any case necessary to reduce the within the company organization, the complex protection system proposed by the multiple anticoronavirus rules produced by the legislator. This not only with the aim of effective worker protection, but also in relation to the responsibilities that could develop in the event of possible coronavirus damage among them.